Exploring risk perception and attitudes to miscarriage and congenital anomaly in rural Western Kenya. - Stephanie Dellicour; Meghna Desai; Linda Mason; Beatrice Odidi; George Aol; Penelope A Phillips-Howard; Kayla F Laserson; Feiko O Ter Kuile (PLoS ONE)
Background Understanding the socio-cultural context and perceptions of adverse pregnancy outcomes is important for informing the best approaches for public health programs. This article describes the perceptions, beliefs and health-seeking behaviours of women from rural western Kenya regarding congenital anomalies and miscarriages. Methods Ten focus group discussions (FGDs) were undertaken in a rural district in western Kenya in September 2010. The FGDs included separate groups consisting of adult women of childbearing age, adolescent girls, recently pregnant women, traditional birth attendants and mothers of children with a birth defect. Participants were selected purposively. A deductive thematic framework approach using the questions from the FGD guides was used to analyse the transcripts. Results There was substantial overlap between perceived causes of miscarriages and congenital anomalies and these were broadly categorized into two groups: biomedical and cultural. The biomedical causes included medications, illnesses, physical and emotional stresses, as well as hereditary causes. Cultural beliefs mostly related to the breaking of a taboo or not following cultural norms. Mothers were often stigmatised and blamed following miscarriage, or the birth of a child with a congenital anomaly. Often, women did not seek care following miscarriage unless there was a complication. Most reported that children with a congenital anomaly were neglected either because of lack of knowledge of where care could be sought or because these children brought shame to the family and were hidden from society. Conclusion The local explanatory model of miscarriage and congenital anomalies covered many perceived causes within biomedical and cultural beliefs. Some of these fuelled stigmatisation and blame of the mother. Understanding of these beliefs, improving access to information about the possible causes of adverse outcomes, and greater collaboration between traditional healers and healthcare providers may help to reduce stigma and increase access to formal healthcare providers.